STUDENTS’ SPECIFIC COMPREHENSION SKILLS IN ENGLISH BASED ON SCHOOL LOCATIONS, GRADES, AND GENDER - Mirizon, Soni; Diem, Chuzaimah Dahlan; Vianty, Machdalena (Universitas Pendidikan Indonesia, 2018)
Having good English proficiency is a necessity in the 21st century and students’ comprehension skills must be identified before any teaching is done. Studies that investigate students’ comprehension skills have been conducted over years but the one related to students’ specific comprehension skills in terms of their school locations, grade levels, and gender has not been much discussed. This study aims at investigating 355 junior high school students’ specific comprehension skills as measured by 18 assessments of Warncke Informal Comprehension Assessment (WICA) Instruments (Warncke Shipman, 1984) based on their school locations (City-based District—CBD, the district which has all levels of education—ALED, and underprivileged-based district—UBD) of Palembang City, grade levels (7th, 8th, 9th) and gender in a developing country context. The findings show that students’ comprehension achievement is in average level with those from CBD neighborhood have better mean score than those from the other two locations respectively and higher graders have higher achievements. In terms of gender, females is better than that of males. While the highest students’ achievements are on multiple meanings and context and details, the lowest one is on affixes, and the most influential factors on comprehension are school locations and grades. These results lead to the conclusion that students’ comprehension should be enhanced and good school environment provided. It also suggests that the degree of difficulty of the materials match students’ grade-level and students be taught using more innovating strategies to achieve the best comprehension and eventually applicable outcome.